Interactions between Organizational Citizenship Behaviors, Interpersonal Trust, Organizational Trust, and Organizational Support - Andrade, Tais; Estivalete, Vania de Fátima Barros; Costa, Vivian Flores; Faller, Lisiane Pellini; Costa, Gabrielle Loureiro (Revista de Administração da UFSM, 2018)
This study aims to analyze the existing relationships between Organizational Citizenship Behaviors, Interpersonal Trust, Organizational Trust and Organizational Support, from the perspective of employees in the educational sector. In order to achieve this objective, a research of character descriptive of the survey type. The instrument filled out by 988 employees was elaborated from the Organizational Citizenship Behavior Scale for Knowledge Workers (OCB-KW), Interpersonal Trust Measure (IT), Employee Trust Scale (ETS) and Organizational Support Perception Scale (OSPS). The main results show the existence of a relationship between the constructs of the social context and the OCB. The highest correlation found between Interpersonal Trust and Organizational Citizenship Behaviors (r=.462), indicating that the existence of trust among the individuals in the organization is directly proportional to their involvement in positive and discretionary behaviors for the common good.